Karawitan : source readings in Javanese gamelan and vocal music. - Becker, Judith, 1932-; Feinstein, Alan H. (Michigan papers on South and Southeast Asia, 1987)
Volume 2, Articles and monographs by Warsodinigrat, Sumarsam, Gitosaprodjo, Purbodiningrat, Poerbatjaraka, Sindoesawarno, and Paku Buwana X.